Perbedaan Kecendrungan Melakukan Ujaran Kebencian (Hate Speech) antara Laki-Laki dan Perempuan - Afdal, Afdal; Ningsih, Tiwi Pertama; Maharani, Utari Khesi; Vanessha, Vanessha; Susanti, Rosi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2021)
Along with the times, especially in the era of the development of information and communication technology. The development of information technology is very sophisticated, fast and easy so that it becomes a lifestyle for people around the world, including Indonesia. The public is free to express their opinions, either through oral, written, print or electronic media (online). Often the delivery of opinions or opinions freely is misused by some people to express their opinions in an uncultured and unethical manner which will bring legal consequences for the perpetrators, one of which is expressing displeasure or making hate speech. Hate speech is an act of communication carried out by an individual or group in the form of provocation, incitement, or insult to another individual or group in terms of various aspects such as race, skin color, gender, disability, sexual orientation, nationality, religion, and others. This hate speech crime can be carried out through various media, including in campaign speeches, social media networks, public presentations (demonstrations), religious lectures and other electronic media. This study aims to see how the differences in the tendency to do hate speech between men and women. The method used in this study is a qualitative descriptive method. This method is used to see and describe the tendency to do hate speech between men and women. This research was conducted on 4 teenagers (2 boys and 2 girls; average age 19 years; student status) through in-depth interviews. The data were analyzed using an interactive model consisting of three steps including data reduction, data presentation and drawing conclusions. The results of the study indicate that there are differences in the forms of hate speech between men and women, where differences in women's hate speech are more provocation to everyone against people who are given hate speech than hate speech committed by men. Therefore, as good Indonesian citizens and upholding unity, in expressing opinions and criticisms, we should use wise and kind sentences, so that our opinions can be accepted and do not cause misunderstandings to other social media users. When using social media services to express opinions and criticisms, we should use wise and kind sentences, so that our opinions can be accepted and do not cause misunderstandings to other social media users. It is better in laws and regulations relating to insults and hate speech, both on social media and in public, a further article is made that explains the intent of hate speech itself, suchas dirty sentences, animal names and speech without valid data. If it is used, it will be subject to the ITE article regarding hate speech itself. Counselors/BK teachers also have an important role to shape student behavior in schools so as not to do hate speech. Not only that, the creativity of a Counselor/BK teacher is also required so that all ways can be taken to avoid students being involved with hate speech behavior by providing information services and providing group guidance services. For students who have been involved with hate speech actions, coaching can be done through individual counseling, group counseling and group guidance.